Using Shakespeare to teach English in the digital age. (7th June 2018) - Seargeant, Philip; Chapman, Catherine
Abstract: This paper examines the opportunities and challenges of using Shakespeare as a teaching resource for English language learners, and reflects on an open distance learning programme aimed at engaging EFL students across diverse world contexts. The paper reviews the design, production, and dissemination of these teaching materials and in doing so discusses how points of language, issues of historical culture, and insights into modern usage can all be addressed in ways that are both entertaining and instructional by reference to Shakespeare's life and works. Additionally, it considers how the harnessing of the transmedia affordances of digital communication can create a broad, interactive experience for students, thus mixing the traditional with the cutting-edge in English language pedagogy.